2012
DOI: 10.1063/1.3672241
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of novel cobaltates Ln0.3CoO2 (Ln = La, Pr, and Nd)

Abstract: Layered cobaltates LnxCoO2 (Ln = La, Pr, Nd; x ∼ 0.30), isostructural with well known thermoelectrics NaxCoO2, have been characterized by diffraction methods and probed by the electric transport, magnetic and heat capacity measurements. The thermopower increases with temperature and saturates above room temperature at a large value ∼ 175 μV/K. The conductivity is affected by occupational disorder and follows Mott’s T−1/n law. The main attention is given to Pr0.3CoO2 and Nd0.3CoO2, in which the spins of hole ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In recent years, a number of novel layered cobaltites with the same CoO 2 block have been prepared by an ionexchange technique from Na x CoO 2 precursor, such as Ca xCoO 2 [10,11], Sr x CoO 2 [12,13], Ba x CoO 2 [14,15] and Ln 0.30 CoO 2 (Ln = La, Pr and Nd) [16,17]. It was reported that they are isostructural to their precursor Na x CoO 2 , and also exhibit a large Seebeck coefficient or low resistivity, which is necessary for a good thermoelectric material.…”
mentioning
confidence: 99%
“…In recent years, a number of novel layered cobaltites with the same CoO 2 block have been prepared by an ionexchange technique from Na x CoO 2 precursor, such as Ca xCoO 2 [10,11], Sr x CoO 2 [12,13], Ba x CoO 2 [14,15] and Ln 0.30 CoO 2 (Ln = La, Pr and Nd) [16,17]. It was reported that they are isostructural to their precursor Na x CoO 2 , and also exhibit a large Seebeck coefficient or low resistivity, which is necessary for a good thermoelectric material.…”
mentioning
confidence: 99%
“…The disadvantage of such artificially grown superlattice materials is that they are not thermodynamically stable structures, reducing their stability at high temperature [15]. A related approach is the use of inherently layered materials, e.g., A x CoO 2 (A = Na, Ca, Sr, Ba, La Pr, Nd) [16,17,18,19,20,21,22]. Such layered materials have a layered structure similar to a superlattice structure and can sustain high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve stable performance from this material system, the monovalent Na + ions should be replaced with divalent Ca 2+ ions, for example by ion exchange method, producing Ca x CoO 2 (0.26 ≤ x ≤ 0.5) thin films [24,25]. The same technique has been reported to be useful to grow a series of layered materials A x CoO 2 (A = Na, Ca, Sr, Ba, La Pr, Nd) [16,17,18,19,20,21,22]. Apart from this ion exchange method, physical [26,27,28,29] methods have also been investigated to grow Ca x CoO 2 thin films.…”
Section: Introductionmentioning
confidence: 99%
“…It was generally supposed that the CdI 2 -type CoO 2 layer along with the natural superlattice structural feature in the layered cobaltites plays a very important role in the thermoelectric properties. 5 In recent years, some other new layered cobaltites, Ca x CoO 2 , 6 Sr x CoO 2 , 7,8 and Ln x CoO 2 (Ln = La, Pr, and Nd), 9,10 synthesized by an ion exchange technique from the Na x CoO 2 precursor 11,12 have been reported to exhibit a large Seebeck coefficient, low resistivity or low thermal conductivity, which are necessary for a good thermoelectric material with a high ZT value (ZT = S 2 σT/κ, where S, σ, κ, and T are the Seebeck coefficient, electrical conductivity, thermal conductivity, and absolute temperature, respectively). For the Ca 0.33 CoO 2 crystal, the resistivity and Seebeck coefficient in the ab-plane are 0.74 mΩ cm and 81 μV K −1 at 300 K, respectively, and the power factor is about 25% higher than that of the Ca 3 Co 4 O 9 crystal.…”
Section: Introductionmentioning
confidence: 99%